PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE BERBANTU SOFTWARE GEOGEBRA VERSI 4.4 DALAM USAHA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS DAN DISPOSISI MATEMATIS SISWA SMP - Erana Erana; Rifqi Hidayat; Desy Lusiyana (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2018)
This research is motivated by the low ability to understand students' mathematicalconcepts and dispositions. The purpose of this study was to determine the increase in theability to understand concepts and differences in mathematical dispositions of studentswho learned using geogebra software assisted learning cycle version 4.4 withconventional learning. This research is a quasi-experimental study. The research designused is Nonequivalent Control Group Design and Purposive Sampling samplingtechnique. The population is class VII students of SMPN 1 Jamblang Cirebon RegencyAcademic Year 2018 / 2019. The research sample involved seventh grade students, 33students in class VII A as the control class and 31 students in class VII B as theexperimental class. Based on the results of the mean post-test difference test using the mann-whitney U test, the Asymp.sig value is generated. (2-tailed) 0,000 <0,05, meaningthat H0 is rejected. Furthermore, the difference test of N-Gain mean with Mann-WhitneyU test obtained Asymp.sig value. (1 -tailed) 0,000 <0,05, ie H0 is rejected. Whereas basedon the results of the mathematical disposition scale using the Independent Sample t-Testproduces a Sig (2-tailed) value of 0.000 <0.05, ie H0 is rejected. The results showed that:(1) The ability to understand mathematical concepts of students learning using theGeogebra software assisted learning cycle version 4.4 is better than students who useconventional learning. (2) Improved understanding of the mathematical concept ofstudents who learn using the Geogebra software assisted learning cycle model version 4.4better than students who study conventionally. (3) The difference in the ability of thestudents' mathematical disposition scale to learn using the Geogebra software assistedlearning cycle model version 4.4 is better than the students who study conventionally.Kata Kunci: Learning cycle, software Geogebra versi 4.4, ability to understandstudents' mathematical concepts and dispositions